On the Name Flail in Pskov District Dialects (in Connection with the “кеп-Problem”) - Чекмонас, В. (Kalbotyra, 1997)
A word form кеп for flail in Pskov dialects (цеп < цѣпъ from common Slavic *koipu / kaipu in another East Slavic dialects) is treated (by M. S. Gliskina, A Zaliznjak and some other scolars) as an evidence of preservation of the velar before the original diphthong. According to the card index of the “Pskov regional dictionary”, кеп was recorded in several localities of Pskov district and adjacent areas. The data collected in sixteen villages show the absence of цеп as a term in this area (and that confirms an information of O. Karmakova). Some facts allow to assume the very realia flail is an ethnographic innovation here. A thorough analysis of an interview in which a form кеп was used by the informants reveals that it can be generated from the new word цеп (derived from the widespread expression цепям мълаmuлu) on the base of usual morphophonemic alternations to avoid cokanje.